SHIP-AGE: Frailty, renal function, and multi-component primary care in rural Mecklenburg-West Pomerania (MV-FIT)- study protocol. - Maik Gollasch; Yulia Komleva; Dmitry Tsvetkov; Felix Morof; Mladen V Tzvetkov; Till Ittermann; Marcus Vollmer; Uta Zahn-Tesch; Holger Kock; Franziska Schuster; Neeltje van den Berg; Henry Völzke; et al. (PLoS ONE, 2025)
Background Chronic kidney disease (CKD) is a leading risk factor for cardiovascular disease and all-cause mortality among older adults. Mecklenburg-West Pomerania has the highest CKD prevalence in Germany and Europe, however, its impact on frailty prevention strategies in primary care remains poorly understood. The SHIP-AGE/MV-FIT study aims to investigate the role of CKD in frailty incidence. Methods The SHIP-AGE/MV-FIT cohort is a prospective, longitudinal, population-based observational study targeting individuals [Formula: see text] 65 years with mGFR >30 mL/min. The cohort will consist of approximately 820 elderly participants who will be monitored over a three-year period. They will undergo a comprehensive, multi-factorial geriatric assessment, along with a structured monitoring and management program aimed at preventing frailty. The program incorporates evidence-based, multi-component care, including physical activity, medication review, nutritional optimization, and fall prevention strategies. Discussion SHIP-AGE/MV-FIT will clarify CKD's role in frailty progression and identify mechanisms underlying frailty and pre-frailty. Additionally, the study aims to implement and evaluate multi-component healthcare strategies for frailty and fall prevention, assess patient adherence and quality of life, and explore elderly individuals' experiences with primary care interventions. By integrating SHIP-AGE data with findings from the SHIP (Study of Health in Pomerania) cohorts in our region, this research will contribute to evidence-based strategies for maintaining health, independence, and well-being in aging populations, particularly in rural primary care settings, such as Mecklenburg-West Pomerania.